Lactate and heart rate responses during swimming at 95 % and 100 % of the critical velocity in children and young swimmers - Filipatou, E.; Toubekis, A.; Douda, H.; Pilianidis, T.; Tokmakidis, S. (Biomechanics and Medicine in Swimming X, 2006)
The purpose of this study was to compare the lactate and heart rate responses of children (n=8, 11.5±0.6 yrs) and young swimmers (n=7, 16.0±1.7 yrs) when swimming at 95% (V95) and 100% (V100) of their critical velocity (CV). On a. series of 4x400m, blood lactate concentration [La] of young swimmers increased at V100 after the 3rd and 4th 400m repetition compared to the 1st (1st:5.55±0.65 vs. 3rd:7.27±1.01 and 4th: 8.02±1.47 mmol/1, p<0.05) but remained unchanged at V95 (p > 0.05). On a series of 4x300m, performed by children, [La] was unchanged after each 300m repetition in both trials (V95 and V100, p>0.05). Heart rate was higher in V100 compared to V95 trial (p<0.05, between groups p>0.05). Swimming at velocity equal to CV increased over time [La] in young swimmers but not in children. This may be attributed to different energetic responses or altered rates of lactate removal in children compared to young swimmers.